HLA-G genetic diversity and evolutive aspects in worldwide populations - Castelli, Erick C. [UNESP]; de Almeida, Bibiana S.; Muniz, Yara C. N.; Silva, Nayane S. B. [UNESP]; Passos, Marília R. S. [UNESP]; Souza, Andreia S. [UNESP]; Page, Abigail E.; Dyble, Mark; Smith, Daniel; Aguileta, Gabriela; Bertranpetit, Jaume; Migliano, Andrea B.; et al. (Springer Nature, 2021)
HLA-G is a promiscuous immune checkpoint molecule. The HLA-G gene presents substantial nucleotide variability in its regulatory regions. However, it encodes a limited number of proteins compared to classical HLA class I genes. We characterized the HLA-G genetic variability in 4640 individuals from 88 different population samples across the globe by using a state-of-the-art method to characterize polymorphisms and haplotypes from high-coverage next-generation sequencing data. We also provide insights regarding the HLA-G genetic diversity and a resource for future studies evaluating HLA-G polymorphisms in different populations and association studies. Despite the great haplotype variability, we demonstrated that: (1) most of the HLA-G polymorphisms are in introns and regulatory sequences, and these are the sites with evidence of balancing selection, (2) linkage disequilibrium is high throughout the gene, extending up to HLA-A, (3) there are few proteins frequently observed in worldwide populations, with lack of variation in residues associated with major HLA-G biological properties (dimer formation, interaction with leukocyte receptors). These observations corroborate the role of HLA-G as an immune checkpoint molecule rather than as an antigen-presenting molecule. Understanding HLA-G variability across populations is relevant for disease association and functional studies.